Antibiotics in Laparoscopic Cholecystectomy: Outcomes in Single versus Multiple Dose Phylaxis in Terms of Surgical Site Infections - Zafar, Muhammad Arslan; Butt, Muhammad Qasim; Ghani, Usman; Azeem , Mansoor Tariq; Farooq, Muhammad Zain; Malik , Ishel Farid (Pakistan Armed Forces Medical Journal, 2024)
Objectives: To study the frequency of surgical site infections post-laparoscopic cholecystectomy in patients receiving a full course of post-operative antibiotics versus a single stat per-operative dose.Study Design: Quasi experimental study.Place and Duration of Study: Department of General Surgery, Pak-Emirates Military Hospital Rawalpindi, Pakistan from Jan to Dec 2020.Methodology: The quasi experimental study involved a total of 798 patients who were planned to undergo Laparoscopic Cholecystectomy. The recruited participants were put into two groups with 399 patients in group-A and 399 patients in group-B. Group-A received a single dose of Ceftriaxone 1g at the time of surgery while group-B received the same drug twice daily for three days. All patients were followed up for two weeks. Data was analyzed using Statistical Package of Social Sciences (SPSS) 26.0.Results: A total of 13(1.6%) patients developed surgical site infections in group-A, while 14(1.7%) occurred in group-B. Of these 5(0.6%) and 8(1.0%) were port site infections, 4(0.5%) and 3(0.3%) patients had fever with no localizing sign, 4(0.5%) and 3(0.3%) developed sub-diaphragmatic abscesses, in group-A and B, respectively. Only one case of peritonitis was seen in group-B, in the whole study. No statistical difference was seen between either group at any point.Conclusion: Administration of a single dose peri-operative antibiotic prophylaxis was not associated with an increase in surgical site infection when compared to multiple dose prophylaxis in patients undergoing laparoscopic cholecystectomy.